Pelvic and endometrial tuberculosis diagnosed during vaginal hysterectomy - Rana, A; Gurung, G; Amatya, A; Koiral, B (Journal of Institute of Medicine Nepal, 2007)
Background: It is indeed unusual to be confronted with cul-de-sac nodularity and exclusive pelvic/ peritoneal miliary deposits at vaginal hysterectomy confounding with endometrial tuberculosis, histology suggestive of chronic granulomatous condtion as an example of genital and peritoneal tuberculosis the rarely which in seen. Keywords: Peritoneal miliary deposits, peritoneal tuberculosis, genital tuberculosis. The full text of this paper is available at Journal of Institute of Medicine website